2022
DOI: 10.3389/fmars.2022.944454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LAI Estimation of Mangrove Communities Using DLR and ELR Algorithms With UAV, Hyperspectral, and SAR Images

Abstract: The high-precision estimation of mangrove leaf area index (LAI) using a deep learning regression algorithm (DLR) always requires a large amount of training sample data. However, it is difficult for LAI field measurements to collect a sufficient amount of sample data in mangrove wetlands. To tackle this challenge, this paper proposed an approach for expanding training samples and quantitatively evaluated the performance of estimating LAI for mangrove communities using Deep Neural Networks (DNN) and Transformer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…RF, GBRT, and XGBoost algorithms are robust in quantitative inversion and are widely used in the estimation of mangrove parameters [15,47,55,56]. In this paper, the feature variables (reflectance bands or combined vegetation indices sensitive to CCC obtained after correlation analysis and feature variable selection) are used as input parame- The reflectance information of GF-6 satellite data is sensitive to vegetation parameters, such as LAI and LCC, and is suitable for estimating parameters related to vegetation growth to monitor vegetation health, so this paper will use GF-6 satellite data to estimate mangrove canopy chlorophyll content information [51][52][53][54].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RF, GBRT, and XGBoost algorithms are robust in quantitative inversion and are widely used in the estimation of mangrove parameters [15,47,55,56]. In this paper, the feature variables (reflectance bands or combined vegetation indices sensitive to CCC obtained after correlation analysis and feature variable selection) are used as input parame- The reflectance information of GF-6 satellite data is sensitive to vegetation parameters, such as LAI and LCC, and is suitable for estimating parameters related to vegetation growth to monitor vegetation health, so this paper will use GF-6 satellite data to estimate mangrove canopy chlorophyll content information [51][52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…RF, GBRT, and XGBoost algorithms are robust in quantitative inversion and are widely used in the estimation of mangrove parameters [15,47,55,56]. In this paper, the feature variables (reflectance bands or combined vegetation indices sensitive to CCC obtained after correlation analysis and feature variable selection) are used as input parameters for the machine learning regression algorithm, with CCC as the target variable.…”
Section: Methodsmentioning
confidence: 99%
“…The Stacking ensemble learning (SEL) algorithm can integrate the advantages of each base model and weaken the effects of overfitting, improving the classification accuracy. It has been confirmed that the SEL algorithm has been successfully applied to crop classification (Sonobe et al, 2018), multi-type flooding delineating (Rahman et al, 2021), mangrove species classification (Fu et al, 2022a), LAI estimation of mangrove communities (Fu et al, 2022b), and other fields. However, the application of the SEL algorithm to waveform classification of altimeters lacks systematic justification.…”
Section: Introductionmentioning
confidence: 94%
“…One is a radiative transfer physical model, and the other is a statistical empirical model. The physical model is based on the reflection and absorption between light and crops, which has a certain mechanism and strong versatility ( Fu et al., 2022a ). However, the model involves complex formulas and requires many parameters, which makes it difficult to find the optimal solution ( Du et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%